The innovative input mix. Assessing the importance of R&D and ICT investments for firm performance in manufacturing and services - Marina Rybalka (Statistics Norway, Research Department, 2015)
Business innovation is an important driver of productivity growth. In this paper, I assess the importance of R&D and ICT investment for firm performance in the manufacturing and service industries. Explicitly, I use an extended version of the CDM model that treats ICT together with R&D as the main inputs into innovation and productivity, and test it on a large unbalanced panel data set based on the innovation survey for Norway. Four different types of innovation and the number of patent applications are used as innovation output measures. I find that ICT investment is strongly associated with all types of innovation in both sectors, with the result being strongest for product innovation in manufacturing and for process innovation in service industries. The impact of ICT on patenting is only positive in manufacturing. Overall, ICT seems to be less important than R&D for innovation, but more important for productivity. These results support the proposition that ICT is an important driver of productivity growth. Given the high rate of ICT diffusion in Norway, my results also contribute to explaining what is referred to as the 'Norwegian productivity puzzle', i.e. the fact that Norway is one of the most productive economies in the OECD despite having relatively low R&D intensity.
Keywords: D24; L60; L80; O3; 330; Innovation; ICT; R&D; Productivity; CDM model; Manufacturing and Services